2023
DOI: 10.1186/s40575-023-00134-z
|View full text |Cite
|
Sign up to set email alerts
|

Is it now time to iron out the wrinkles? Health of Shar Pei dogs under primary veterinary care in the UK

Dan G. O’Neill,
Karolina S. Engdahl,
Alice Leach
et al.

Abstract: Background The Shar Pei is a common dog breed with a distinctive appearance caused by hyaluronosis that has been linked with several health conditions. Anonymised primary-care veterinary clinical records were explored to extract data on the demography, common disorders and mortality of Shar Pei in the UK in 2013. Results The study population of 455,557 dogs included 1913 (0.42%) Shar Pei. The mean adult bodyweight was 22.26 kg. The most prevalent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Hypertypes of several dog breeds including the French Bulldog, Bulldog and Shar pei have excessive skin folds that predispose them to recurrent and chronic dermatitis and pyoderma [32][33][34]. Although it is possible to treat these conditions they are nevertheless painful and many may not be addressed because owners frequently do not recognize the clinical signs (37% of owners of English Bulldogs in a Finnish survey [32,35]).…”
Section: Dogsmentioning
confidence: 99%
“…Hypertypes of several dog breeds including the French Bulldog, Bulldog and Shar pei have excessive skin folds that predispose them to recurrent and chronic dermatitis and pyoderma [32][33][34]. Although it is possible to treat these conditions they are nevertheless painful and many may not be addressed because owners frequently do not recognize the clinical signs (37% of owners of English Bulldogs in a Finnish survey [32,35]).…”
Section: Dogsmentioning
confidence: 99%
“…Entropion is an ophthalmic condition characterized by the partial or complete inversion of the eyelid margin, being highly prevalent in certain canine breeds, especially among brachycephalics [1,2]. A study conducted by OʹNeill et al [3], revealed that, in a population of 455,557 Shar Pei patients (brachycephalics), the prevalence of entropion reached 17.88%. Continuing this trend, Costa et al [4] reported a prevalence of 22% out of a sample of 98 brachycephalic canines.…”
Section: Introductionmentioning
confidence: 99%